Pulmonary Embolism Treatment: Current Developments and Approaches - Evren Dal; Suna Eraybar; Mehtap Bulut; Akkan Avcı (Global Emergency and Critical Care)
Pulmonary embolism (PE) remains an important preventable condition with high mortality and morbidity, recurrence, and sometimes difficult diagnosis. Current treatments have evolved considerably and changed remarkably recently. PE is a condition requiring critical care, and rapid advances in this field have led to significant evolution in treatment strategies. The broad spectrum and severity of PE require individualization and optimization of treatment approaches. In addition to algorithms guiding the diagnostic process of patients, the use of risk classifications guiding the recognition of critically ill patients and the decision of treatment modalities has an important place in emergency department practice. This review addresses the latest developments for treating PE based on the current findings of epidemiological studies. Considering the characteristics of patient populations, clinical conditions, and comorbidities, a range of treatment options from anticoagulation therapies to catheter-based interventions, thrombolytic therapies, and alternative approaches will be examined. Changes in current guidelines affecting treatment decisions and the role of a multidisciplinary approach will also be emphasized. This review aims to synthesize the current knowledge in the field of PE treatment and will allow us to collectively interpret the most effective and safe treatment strategies for this critical condition.